Knowledge, practices and perceptions of trachoma and its control among communities of Narok County, Kenya. Issue 1 (December 2016) - Njomo, Doris; Karimurio, Jefitha; Odhiambo, Gladys; Mukuria, Mukiri; Wanyama, Ernest; Rono, Hillary; Gichangi, Micheal
Abstract Background Trachoma is the leading infectious cause of blindness in the world. It is commonly found in cultural groups with poor hygiene. Trachoma control includesS urgery, A ntibiotics, F acial cleanliness andE nvironmental Improvement (SAFE). Potentially blinding and active trachoma are monitored using trachomatous trichiasis (TT) in adults and trachoma inflammation-follicular (TF) in children aged 1–9 years respectively. A cross-sectional study to assess the knowledge, practices and perceptions of trachoma and its control was conducted in the endemic communities in Narok County. Methods Qualitative methods were used for data collection. Using purposive sampling, 12 focus group discussions (FGDs) with single sex adult and young men and women groups of homogenous characteristics, 12 key informant interviews with opinion leaders and 5 in-depth interviews (IDIs) with trichiasis patients and 6 with persons who have undergone trichiasis surgery were conducted. Data was audio recorded, transcribed, coded and analyzed manually by study themes; knowledge, practices and perceptions of trachoma transmission, infection signs, prevention and control. Results Majority of the community members had knowledge of trachoma and its transmission. The practices that contributed to transmission of infection included: failure to wash faces and bathe regularly, sharing of water basins and towels for face washing, traditional methods of trachoma treatment and dirty household environment. Due to socio-cultural perceptions, toilets were unacceptable and use of bushes for human waste disposal was common. Poor perceptions on disease susceptibility, flies on children's faces, latrine ownership and usage and separation of human and animal dwellings also played a role in the transmission of trachoma. Fear of loss of sight during surgery was a deterrent to its uptake and a desire to be able to see and take care of domestic animals promoted surgery uptake. Majority of the community members were appreciative of Mass Drug Administration (MDA) though side effect such as vomiting and diarrhoea were reported. Conclusion Poor practices and related socio-cultural perceptions are important risk factors in sustaining trachoma infection and transmission. Community members require health education for behavior change and awareness creation about surgery, MDA and its potential side effects for elimination of trachoma in Narok County, Kenya. Trial registration KEMRI SSC 2785 . Registered 2 September 2014.